An Evaluation Model of Problem-Based Learner Assessment in Curriculum 2013 - Yunita Rizky Wijayanti (Magister Kajian Bahasa Inggris (English Language Studies) Universitas Sanata Dharma Yogy, 2015)
Curriculum 2013 has just been implemented at schools in Indonesia, and its implementation has brought pros and cons among academicians. One of the major constructive criticisms related to the implementation of curriculum 2013 deals with the application of the creation. Bloom claims that creating places the top level among the thinking skills (Pohl, 2000). Furthermore, Dyers (2011) states that the main goal of each learning process is to improve the learners‟ creativity. This paper focuses on the evaluation of learner assessment; hence, it aims to propose an alternative model of learner assessment based on curriculum 2013 by focusing on the concept of scientific approach especially on creation and also the concept of positivism. Moreover, the result of Forum Group Discussion (FGD) shows positive feedback. The findings obtained from FGD generally show more positive feedback than the negative one. In brief, it can be concluded that the model has been better because it provides creation, clear description, and it may encourage building positive characters of the learners.